Mapping and assessing black pepper growth using time series and ground data: a case study for small scale cultivation in Bintulu, Sarawak - Zainol, W. N. Z.; Kamsan, S. Z. L.; Che'Ya, N. N. (IOP Publishing, 2022)
Mapping of crop cultivation using remote sensing immensely facilitate crop management and prediction. The capability to provide informative data enables users to monitor and manage their crops with optimum expenditure. Hence, this study was purposed on black pepper farm to establish an informative map of black pepper farm (SF, TF) in Sungai Plan, Bintulu, Sarawak using Landsat 8 OLI time series and ground truth data. Images from Landsat 8 OLI were retrieved and images were classified using Support Vector Machine (SVM). Extraction of farmland elevations was produced using black pepper points collected and processed through ArcGIS 10.4 software. Black pepper growth was measured through the percentage of height and DBH developed throughout this study. It was identified in this study that; (1) mapping black pepper farm using Landsat 8 OLI and SVM provides overall accuracy >70% and Kappa Coefficient >60% and, (2) the optimum black pepper growth was observed at elevation range between 39m - 50m. This study demonstrated that detailed information on geography and black pepper growth can enhance black pepper productivity and management.